Neuronal cilia in energy homeostasis - Brewer, Kathryn M.; Brewer, Katlyn K.; Richardson, Nicholas C.; Berbari, Nicolas F. (Frontiers in Cell and Developmental Biology, 2022)
A subset of genetic disorders termed ciliopathies are associated with obesity. The mechanisms behind cilia dysfunction and altered energy homeostasis in these syndromes are complex and likely involve deficits in both development and adult homeostasis. Interestingly, several cilia-associated gene mutations also lead to morbid obesity. While cilia have critical and diverse functions in energy homeostasis including their roles in centrally mediated food intake and peripheral tissues, many questions remain. Here, we briefly discuss syndromic ciliopathies and monogenic cilia signaling mutations associated with obesity. We then focus on potential ways neuronal cilia regulate energy homeostasis. We discuss the literature around cilia and leptin-melanocortin signaling and changes in ciliary G protein-coupled receptor (GPCR) signaling. We also discuss the different brain regions where cilia have been implicated in energy homeostasis and the potential for cilia dysfunction in neural development to contribute to obesity. We close with a short discussion on the challenges and opportunities associated with studies looking at neuronal cilia and energy homeostasis. This review highlights how neuronal cilia-mediated signaling is critical for proper energy homeostasis.